Unique nonclinical safety profile of PF-06835919, a ketohexokinase inhibitor, highlights a species-dependent mechanism - Jun Zhou; Christopher Houle; Frank J. Geoly; Sarah N. Campion; Jon Cook (Regulatory Toxicology and Pharmacology, 2026)

Thyroid dysregulation underlies altered ovarian cyclicity in rats exposed to PF-06835919, a ketohexokinase inhibitor - Sarah N. Campion; Christopher J. Bowman; Christopher Houle; Jessie Qian; Jun Zhou; Jon Cook (Reproductive Toxicology, 2026)

Climate effects of management intensity and rotation length for planted pine systems - Sarah J. Puls; Justin S. Baker; Rachel L. Cook; James L. Rakestraw (Mitigation and Adaptation Strategies for Global Change, 2026)
Managed forests, including plantation systems, play a vital and often underappreciated role in contributing to the global carbon sink and mitigating climate change, and determining the most effective mitigation strategies requires accounting methods that accurately assess the climate effects of forests. We use a dynamic life cycle assessment methodology to compare the climate effects of thirty-six forest management scenarios (varying site productivity, planting density, fertilization, and thinning) with varying rotation lengths for loblolly pine plantations in the southern U.S., including both in situ and ex situ greenhouse gas fluxes. We also evaluate the effectiveness of using only carbon stock estimates to assess the net climate effect of a given management regime relative to radiative forcing metrics. Carbon stocks alone failed to accurately portray the climate effects from different management regimes, emphasizing the need for greenhouse gas accounting methodologies that directly represent the effect of forest management on potential atmospheric warming mitigation efforts. When radiative forcing is used for comparison, our results show that management decisions such as thinning and rotation length should be adjusted based on stand-specific conditions, and that overgeneralized strategies, such as extending rotation lengths, had little effect on net radiative forcing for many scenarios.

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Understanding the influence of environmentally persistent free radical location on reactive oxygen species generation in soils - Myron L. Lard; Sarah E. Eichler; Lavrent Khachatryan; Randall Hall; Stephania A. Cormier; Robert L. Cook; Jennifer Richmond-Bryant (Chemosphere, 2026)

Genes Versus Environment: Body Size Variation Among Recruitment Cohorts of Dungeness Crab - James L. Dimond; Sarah K. Grossman; Emily V. Buckner; Claire E. Cook; Katelyn M. Bosley; Elizabeth D. Tobin; Julie S. Barber (Molecular Ecology, 2026)
Understanding the drivers of phenotypic variation is key to disentangling the evolutionary and environmental forces that shape patterns of trait variation within and among populations. In Dungeness crab, settlement‐stage megalopae exhibit striking seasonal variation in body size, with early season cohorts consistently larger than later ones. This pattern may result from genetically distinct larval sources or environmentally induced plasticity following the temperature–size rule, which predicts larger body size at cooler temperatures. Here, we evaluated the relative contributions of these potential drivers by analysing megalopae size, regional sea surface temperatures and whole‐genome resequencing data from megalopae collected across the ~5‐month settlement season throughout Washington, USA. Genomic analyses revealed a subtle coastal ancestry signal in early‐arriving megalopae, supporting the hypothesis that these megalopae are of coastal origin. Coastal ancestry was associated with larger megalopae, even after accounting for temperature; however, temperature was a stronger predictor, with a standardised effect size more than three times greater than that of ancestry. A genome‐wide association study found no significant associations with megalopae size, suggesting the absence of a strong genotype–phenotype relationship or a lack of statistical power to detect a highly polygenic trait. Together with prior laboratory rearing studies, our findings support a dominant role for environmentally driven plasticity in body size variation. Persistent cohort differences previously observed in juvenile and adult body size raise the possibility that thermal conditions during early life may promote a carryover effect with potentially significant demographic and fishery implications.

Correction: Cutaneous α-Synuclein Pathology as a Differential Marker: A Histological and Statistical Comparison across Neurodegenerative Disease Groups - Dorota Šebelová; Kateřina Menšíková; Michaela Kaiserová; Lenka Satke; Zuzana Grambalová; Kateřina Čížková; Zdeněk Tauber; Kateřina Klíčová; Dominik Hraboš; Sarah E. V. Cook; Jana Zapletalová; Petr Kaňovský (Journal of Molecular Neuroscience, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Investigating the effects of biogenic amines on the dominance hierarchy in the small carpenter bee, Ceratina calcarata - Riya N. Miller; Sandra M. Rehan; Chelsea N. Cook; Colin S. Brent; Sarah P. Lawson (Insectes Sociaux, 2026)
Biogenic amines are highly conserved across animal species and aid in the regulation of movement, behavior, motivation, temperature, blood pressure, and endocrine secretion. Within eusocial species, such as the honey bee Apis mellifera , biogenic amines are responsible for modulating traits associated with higher levels of sociality, such as division of labor. In Ceratina calcarata , a facultatively social bee species, mothers establish a dominance hierarchy over their eldest daughter by providing them with less pollen and less protein, resulting in smaller, more submissive adults referred to as dwarf eldest daughters (DEDs). We hypothesized that this dominance hierarchy is additionally modulated by biogenic amines. To examine this hypothesis, we first compared biogenic amine levels between mothers and daughters and found significantly higher levels of dopamine, octopamine and tyramine in the mothers. To quantify the effects of these biogenic amine differences, dopamine was topically administered to C. calcarata DEDs, while the mothers were topically treated with the dopamine blocker cis-(Z)-Flupentixol dihydrochloride. Aggression helps to establish social hierarchies, so mothers and DEDs from the same nest underwent behavioral assays to assess aggressive and tolerant behaviors. When dopamine was blocked in the naturally more aggressive mothers, there was no difference in the number of aggressive interactions. Instead, treated mothers became more tolerant of DEDs, indicating dopamine plays a key role in modulating these behaviors. More work is needed to understand the different roles each biogenic amine plays in the development of a dominance hierarchy, especially in these species on the brink of eusociality.

Cutaneous α-Synuclein Pathology as a Differential Marker: A Histological and Statistical Comparison across Neurodegenerative Disease Groups - Dorota Šebelová; Kateřina Menšíková; Michaela Kaiserová; Lenka Satke; Zuzana Grambalová; Kateřina Čížková; Zdeněk Tauber; Kateřina Klíčová; Dominik Hraboš; Sarah E. V. Cook; Jana Zapletalová; Petr Kaňovský (Journal of Molecular Neuroscience, 2026)
There is an urgent need for early and accurate biomarkers of neurodegenerative disorders. Due to the high innervation and accessibility of the skin, a skin biopsy is a minimally invasive method of detecting phosphorylated α-synuclein (p-α-syn) and assessing intraepidermal nerve fiber density (IENFD). We analyzed biopsies taken from the back and the leg of patients with parkinsonian syndromes (Park.sy.), α-synucleinopathies, multiple system atrophies (MSA), tauopathies, and other neurological disorders, as well as from healthy controls. Double immunofluorescence was performed for p-α-syn (Ser129) and protein gene product 9.5 (PGP 9.5), alongside quantitative IENFD assessment. p-α-syn was significantly more prevalent in the patient groups than in the control group. The highest prevalence was observed in patients with parkinsonian syndromes, α-synucleinopathies and MSA. Tauopathies showed preferential paravertebral positivity. Reduction or absence of IENFD was most pronounced in tauopathies (75%), while IENFD was most commonly preserved in MSA (83.3%), indicating that disease-specific patterns of peripheral nerve involvement are exhibited. p-α-syn positivity was found to correlate with shorter disease duration, suggesting its potential as an early biomarker. Combined with olfactory testing, cutaneous markers improved diagnostic discrimination. Our findings support the use of skin biopsies as a promising clinical tool in diagnosing biomarker-based neurodegenerative diseases.

Collaborative evaluation of in silico predictions for high throughput toxicokinetics - John F. Wambaugh; Nisha S. Sipes; Gilberto Padilla Mercado; Jon A. Arnot; Linda Bertato; Trevor N. Brown; Nicola Chirico; Christopher Cook; Daniel E. Dawson; Sarah E. Davidson-Fritz; Stephen S. Ferguson; Michael-Rock Goldsmith; et al. (Toxicology in Vitro, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Examining Explicit Stereotype Perceptions of Colorectal Cancer Screening and Diagnosis in the Hispanic Community - Aidan Foley; Bianca Luna-Lupercio; Jessica M. Capaldi; Galen Wiens-Cook; Vinicius Calsavara; Zulfikarali Surani; Sarah-Jeanne Salvy; Jane C. Figueiredo; Robert Haile; Nenette A. Cáceres; Celina H. Shirazipour (Journal of Cancer Education, 2025)
Cancer is a leading cause of death among Hispanic people in the USA. One potential reason is low adherence to cancer screening guidelines, particularly for colorectal cancer (CRC). Previous research suggests that low CRC screening may be linked to negative stereotypes associated with cancer and CRC screening methods. The purpose of this study was to examine explicit stereotype perceptions of CRC screening and diagnosis in the Hispanic community. Hispanic adults ( n = 279) were asked to read three vignettes presenting a gender-neutral individual who was either diagnosed with CRC, completed colonoscopies for CRC screening, or was a control (no cancer information provided). Using the Stereotype Content Model approach, after reading each vignette, participants completed measures assessing explicit perceptions (warmth and competence) of the individual. Linear mixed-effects models were fitted to evaluate differences in perceptions between vignettes. The main effect indicated no significant difference in warmth or competence perceptions based on vignette condition ( p = .78). However, there was a significant difference in explicit perceptions based on the study participant’s Hispanic heritage, gender, and age ( p s < .05). Findings emphasize differences in explicit perceptions of cancer and cancer screening based on important demographic characteristics. Thus, important implications include the need for cancer educational materials and interventions to consider the important heterogeneity within the Hispanic community. Future CRC screening interventions should be tailored based on Hispanic heritage, gender, and age.

First record of a piebald leucistic smallspotted catshark Scyliorhinus canicula in a special area of conservation, UK - Neil D. Cook; Sarah L. Perry; Declan T. G. Quigley; Jo Cable; Sarah E. Perkins (Marine Biodiversity, 2025)
Colour aberrations are widely reported in vertebrates, but seldom for elasmobranchs. Shark trophic level varies ontogenetically and according to species, so atypical colouration may have implications for ecological fitness both as predator and prey. Here, we present, to our knowledge, the first and only record of a piebald leucistic smallspotted catshark Scyliorhinus canicula from Welsh waters, specifically in the Cardigan Bay Special Area of Conservation, UK. This adds to the five previous observations from the Irish and Mediterranean Seas. Sharks face numerous threats, including the physiological impacts of climate change. In this context, the prevalence and implications of leucism remain a knowledge gap.

The state and fate of noble metals in bornite and digenite - Samuel A. King; Cristiana L. Ciobanu; Nigel J. Cook; Ashley D. Slattery; Sarah E. Gilbert; J. Richard Kyle; Kathy Ehrig; Jie Yao (Lithos, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Four unusual mortality events of seabirds in the Patagonian Sea, 2000–2006: species affected and possible causes - Marcela M. Uhart; Ralph E. T. Vanstreels; Flavio Quintana; Belén Mattera; Nora Montoya; Leonardo Guzman; Hernan Pacheco Valles; Gemita Pizarro; Carolina A. Marull; Luciana Pozzi; Torsten Mörner; Pablo García-Borboroglu; et al. (Polar Biology, 2025)
The Patagonian Sea is a highly productive marine ecosystem and a hotspot for seabird diversity and density in the Southwest Atlantic Ocean. Reports of unusual mortality events are relatively scarce in this region, likely due to under detection and investigation. In this study, we report on four unusual mortality events affecting seabirds in the Patagonian Sea from 2000 to 2006. Events 1 and 2 occurred at Golfo Nuevo and Chubut coast, Argentina in September–December 2000, affecting at least 4550 seabirds, mainly Magellanic penguins ( Spheniscus magellanicus ). Event 3 occurred at the Falkland/Malvinas Islands during December 2002–January 2003, affecting at least 3500 seabirds, mainly gentoo penguins ( Pygoscelis papua ). Event 4 occurred at Punta Loma and Punta León, Argentina, in November 2006, affecting at least 57 seabirds, mainly kelp gulls ( Larus dominicanus ). The aetiology of Events 1 and 2 could not be determined, but malnutrition/starvation and paralytic shellfish poisoning, respectively, were identified as potential causes. Pathological findings and toxicological testing supported paralytic shellfish poisoning as the cause of Events 3 and 4. Our results illustrate how identifying the occurrence, cause and extent of unusual mortality events affecting seabirds can present significant challenges. Moreover, our investigations of the events display variations in timeliness and completeness, and our lack of certainty on aetiology reflects the shortcomings often faced in remote locations and low resource settings. Technological advances, such as smartphones, increased public awareness and connectivity, coupled with more and better equipped protected areas and diagnostic laboratories will likely aid in overcoming difficulties from past decades.

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Fact-based environmental messaging did not influence Australians' attitudes and intentions towards cultivated seafood - Sarah J. Cook; Adam P.A. Cardilini; Alexa Hayley; Prue Francis (Food Quality and Preference, 2025)

Ecosystem-wide PFAS characterization and environmental behavior at a heavily contaminated desert oasis in the southwestern U.S. - Jean-Luc E. Cartron; Chauncey R. Gadek; Jonathan L. Dunnum; Christopher C. Witt; Mariel L. Campbell; Samuel J. Romero; Andrew B. Johnson; Julie Kutz; Christopher Wolf; Sarah J. Choyke; Joseph A. Cook (Environmental Research, 2025)

Trace element distributions among Cu-(Fe)-sulfides from the Olympic Dam Cu-U-Au-Ag deposit, South Australia - Samuel A. King; Nigel J. Cook; Cristiana L. Ciobanu; Kathy Ehrig; Sarah Gilbert; Benjamin Wade; Yuri T. Campo Rodriguez (Mineralium Deposita, 2025)

Vertebral elemental composition reveals ontogenetic changes in habitat use in a Northeast Atlantic mesopredator shark - Neil D. Cook; Ana Samperiz; Morten Andersen; Edward Inglis; Marc-Alban Millet; Jo Cable; Sarah E. Perkins (Estuarine, Coastal and Shelf Science, 2025)

Coupled Lu-Hf and U-Pb apatite geochronology of Jatobá orebody supports ∼ 2.5 Ga metamorphism in deep shear zones from southern Copper Belt, Carajás Domain, Brazil - Yuri Tatiana Campo-Rodriguez; Cristiana L. Ciobanu; Sarah Gilbert; Benjamin Wade; Nigel J. Cook; Maria Emilia Schutesky; Kathy Ehrig (Precambrian Research, 2025)

Monazite, lanthanide-rich glasses, and other trace elements in copper smelter slags: constraints on critical metal behaviour in Si-Fe-rich melts - Hassan Gezzaz; Cristiana L. Ciobanu; Nigel J. Cook; Kathy Ehrig; Ashley Slattery; Benjamin Wade; Sarah Gilbert; Yuri T. Campo Rodriguez (Mineralogy and Petrology, 2025)
Furnace slags are potential new sources of critical metals. We undertook a micron- to nanoscale study that addresses speciation, distribution and associations of phases in air-cooled flash furnace (FF, oxidised) and electric furnace (EF, reduced) slags from the Olympic Dam mining-smelting-refinery operation. Results enable understanding of the behaviour and partitioning of critical metals between melt and cooling crystalline phases in a controlled smelter environment that mimics Fe-Si-rich systems in Nature. Melts at ~ 1300 °C result in slags that differ in the relative proportions of component phases. Both FF and EF slags comprise major magnetite and two, compositionally distinct Si-Fe-rich glasses (glass-1 and -2); fayalite is a main component of EF slag. Glass-1 is rich in REE + Y (4.5–5.4 wt%, Ce 2 O 3 + La 2 O 3 ) and contains dendritic monazite-(Ce). Glass-2 (~ 70 wt% SiO 2 ) contains < 1 wt% Ce 2 O 3 + La 2 O 3 . The EF slag reaction sequence is: magnetite $$→$$ → fayalite + glass-1 $$→$$ → monazite $$→$$ → glass-2. Immiscibility of REE-rich liquid from Si-Fe-rich melt is inferred from amorphous ‘monazite-like’ droplets. Chondrite-normalised fractionation patterns are defined by downwards-sloping LREE segments in both glasses. Partition coefficients are calculated for magnetite and fayalite relative to glasses. D REY for HREE exceeds those for LREE in all phases and fayalite has an order of magnetite higher D HREE than co-existing EF magnetite. Applying lattice strain models to experimental values show excellent fits for D HREE-model trends, even if lattice strain is not the sole factor controlling partitioning. Melt polymerisation, variable/unpredictable oxidation states, and constraints from specific crystallographic sites, also impact on observed trends. This study provides clues to element behaviour in metallurgical plants that can assist potential utilization of copper smelter slags to meet the demand for REE and other contained critical metals.

STICr: An open-source package and workflow for stream temperature, intermittency, and conductivity (STIC) data - Sam Zipper; Christopher T. Wheeler; Delaney M. Peterson; Stephen C. Cook; Sarah E. Godsey; Ken Aho (Environmental Modelling & Software, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Remotely Sensed Fire Heterogeneity and Biomass Recovery Predicts Empirical Biodiversity Responses - Rebecca K. Gibson; Don A. Driscoll; Kristina J. Macdonald; Grant J. Williamson; Rachael H. Nolan; Tim S. Doherty; Dale G. Nimmo; Euan G. Ritchie; Mark Tozer; Liz Tasker; Aaron Greenville; Adam Roff; et al. (Global Ecology and Biogeography, 2025)
Aim To compare field‐based evidence of plant and animal responses to fire with remotely sensed signals of fire heterogeneity and post‐fire biomass recovery. Location South‐eastern Australia; New South Wales. Time Period 2019–2022. Major Taxa Studied A total of 982 species of plants and animals, in eight taxonomic groups: amphibians, birds, fish, insects, mammals, molluscs, plants and reptiles. Methods We collated 545,223 plant and animal response records from 47 field surveys of 4613 sites that focussed on areas burnt in 2019–2020. For each site, we calculated remotely sensed signals of fire heterogeneity and post‐fire biomass recovery, including the delayed recovery index. Meta‐regression analyses were conducted separately for species that declined after fire (negative effect sizes) and species that increased after fire (positive effect sizes) for each buffer size (250 m, 500 m, 1 km, 1.5 km, 2 km and 2.5 km radius). Results We found that species exposed to homogenous high‐severity fire (i.e., low fire heterogeneity) were more likely to exhibit decreased abundance/occurrence or inhibited recovery. Areas with delayed recovery of biomass also had significant negative on‐ground responses, with lower abundance or occurrence in areas where biomass recovery was slower. Main Conclusions The fire heterogeneity index and the delayed recovery index are suitable for inclusion in monitoring and reporting systems for tracking relative measures over time, particularly when field survey data is not available at the landscape scales required to support reporting and management decisions. Locations with remotely sensed signals of delayed recovery should be prioritised for protection against further disturbances that may interfere with the recovery process. Research attention must next focus on how cumulative fire heterogeneity patterns of successive fires affect the post‐fire recovery dynamics to further inform the application of remote sensing indicators as management tools for biodiversity conservation.

Microplastic pollution in salt marsh and urban tributary sediment cores of the River Thames estuary, UK: Spatial and temporal accumulation trends - Megan M. Trusler; Sarah Cook; Barry H. Lomax; Christopher H. Vane (Marine Pollution Bulletin, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Mineralogy, mineral chemistry, and genesis of Cu-Ni-As-rich ores at Lisheen, Ireland - Max Frenzel; Markus Röhner; Nigel J. Cook; Sarah Gilbert; Cristiana L. Ciobanu; John F. Güven (Mineralium Deposita, 2025)
The Irish Orefield is characterised by the presence of both Zn-Pb- and Cu-Ni-As-rich deposits, prospects, and orebodies in similar structural and stratigraphic positions. However, the genetic relationships between these mineralisation types are still debated. In this article, we present new mineralogical, paragenetic, and mineral-chemical observations from the Cu-Ni-As-rich ores at the classic Lisheen deposit, County Tipperary. These observations indicate the intimate association and cogenetic nature of these ores with the more abundant Zn-Pb-rich mineralisation. Specifically, both mineralisation types appear to have formed at the same time, under similar physicochemical conditions, and from the same ore fluids. In addition, both types of mineralisation contain elevated Ge contents. The cogenetic nature of the two mineralisation types, the relative absence of Cu-Ni-As-rich ores from most of the larger Irish-type Zn-Pb deposits compared to expectations derived from probable ore fluid compositions, and finally, the known geological characteristics of larger Cu-Ni-As-rich ore bodies, like Gortdrum, indicate that significant Cu-Ni-As-rich mineralisation could be present at lower stratigraphic levels across the Irish Orefield. Areas with extensive known Zn-Pb mineralisation are expected to be particularly prospective for such ores, which may occur at stratigraphic levels as deep as the Old Red Sandstone. This may have additional implications beyond Ireland, and could point to the potential for undiscovered Cu-rich ores in low-temperature carbonate-hosted Zn-Pb districts elsewhere.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Comparing efficiencies of population control methods for responding to introductions of transboundary animal diseases in wild pigs - Nathan P. Snow; Benjamin Smith; Michael J. Lavelle; Michael P. Glow; Kayleigh Chalkowski; Bruce R. Leland; Sarah Sherburne; Justin W. Fischer; Keely J. Kohen; Seth M. Cook; Hatton Smith; Kurt C. VerCauteren; et al. (Preventive Veterinary Medicine, 2024)

Modeling growth of multiple recruitment cohorts of Dungeness crab co-occurring within the central Salish Sea - Claire E. Cook; Sarah K. Grossman; Julie S. Barber (Journal of Experimental Marine Biology and Ecology, 2024)

Microplastics pollution in sediments of the Thames and Medway estuaries, UK: Organic matter associations and predominance of polyethylene - Megan M. Trusler; Vicky L. Moss-Hayes; Sarah Cook; Barry H. Lomax; Christopher H. Vane (Marine Pollution Bulletin, 2024)

Threat assessment for Pacific sand lance (Ammodytes personatus) in the Salish Sea - Jacqueline R. Huard; Victoria Hemming; Matthew R. Baker; Jennifer Blancard; Ian Bruce; Sarah Cook; Gail K. Davoren; Phillip Dionne; Virginia East; J. Mark Hipfner; Nicola R. Houtman; Brian A. Koval; et al. (Frontiers in Marine Science, 2024)
Like many forage fish species, Pacific sand lance ( Ammodytes personatus ) play a key role in nearshore marine ecosystems as an important prey source for a diverse array of predators in the northeastern Pacific. However, the primary threats to Pacific sand lance and their habitat are poorly defined due to a lack of systematic data. Crucial information needed to assess their population status is also lacking including basic knowledge of their local and regional abundance and distribution. Sand lance are currently listed as ‘not evaluated’ under the IUCN red list and they have not been assessed by US and Canadian agencies. This hampers management and policy efforts focused on their conservation. To address this knowledge gap, we conducted a three-part, structured expert elicitation to assess the vulnerability of Salish Sea sand lance populations. Experts were asked to list and rank key threats to Salish Sea sand lance and/or their habitat, to further quantify the vulnerability of sand lance to identified threats using a vulnerability matrix, and to predict the population trajectory in 25 years from today. Impacts associated with climate change (e.g. sea level rise, sea temperature rise, ocean acidification, and extreme weather) consistently ranked high as threats of concern in the ranking exercise and quantified vulnerability scores. Nearly every expert predicted the population will have declined from current levels in 25 years. These results suggest sand lance face numerous threats and may be in decline under current conditions. This research provides vital information about which threats pose the greatest risk to the long-term health of sand lance populations and their habitat. Managers can use this information to prioritize which threats to address. Future research to reliably quantify population size, better understand the roles of natural and anthropogenic impacts, and to identify the most cost-effective actions to mitigate multiple threats, is recommended.

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Temporal niche partitioning as a potential mechanism for coexistence in two sympatric mesopredator sharks - Neil D. Cook; Abbie Jenkins; Sarah L. Perry; Sarah E. Perkins; Jo Cable (Frontiers in Marine Science, 2024)
Global marine biodiversity declines require bold and ambitious plans to safeguard ecosystem services. Overfishing, habitat loss and projected climate impacts have yielded deleterious effects on marine predators, in particular, driving increasing threat of extinction for many shark species with implications for ecosystem health. Identifying and protecting critical habitat areas for sharks is fundamental to their protection, and may allow for species recovery. Here we use baited remote underwater video stations to investigate spatial and temporal patterns of habitat use by sharks in a Special Area of Conservation (SAC) that is centrally important to the regional blue economy in the UK, the Cardigan Bay SAC. Our results show heterogeneous spatial habitat use and temporal trends in habitat sharing between smallspotted catsharks Scyliorhinus canicula and nursehounds S. stellaris . Nearshore reef habitats are substantially more important than non-reef habitats for both species. The relative abundance of each species, however, is roughly inversely seasonally proportional, with S. canicula and S. stellaris relative abundance highest in March and September, respectively. Temporal niche partitioning may be an important mechanism in marine systems, but has not been widely investigated in sympatric shark communities. These findings are directly relevant for ongoing development of the Welsh Marine Evidence Strategy (2019-2025) and the Welsh National Marine Plan, particularly to inform spatial planning to strengthen the role of SAC management design in protecting important shark areas.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Wastewater reuse and pharmaceutical pollution in agriculture: Uptake, transport, accumulation and metabolism of pharmaceutical pollutants within plants - Md Khaled Mosharaf; Rachel L. Gomes; Sarah Cook; Mohammed S. Alam; Amanda Rasmusssen (Chemosphere, 2024)

Trace element impurities in anode copper from Olympic Dam, South Australia - Nigel J. Cook; Kathy Ehrig; Cristiana L. Ciobanu; Sarah E. Gilbert; Hassan Gezzaz (Minerals Engineering, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Development of an open-source carbon footprint calculator of the UK craft brewing value chain - Alexander L. Bowler; Sarah Rodgers; Fanran Meng; Jon McKechnie; David J. Cook; Nicholas J. Watson (Journal of Cleaner Production, 2024)

Implications for metallogenic evolution of the giant Zhenyuan gold deposit (Yunnan, SW China) from textures and geochemical compositions of pyrite - Huichao Zhang; Nigel J. Cook; Hongrui Zhang; Zengqian Hou; Peng Chai; Wei Li; Sarah Gilbert (Contributions to Mineralogy and Petrology, 2024)

Simulating carbon accumulation and loss in the central Congo peatlands - Dylan M. Young; Andy J. Baird; Paul J. Morris; Greta C. Dargie; Y. Emmanuel Mampouya Wenina; Mackline Mbemba; Arnoud Boom; Peter Cook; Richard Betts; Eleanor Burke; Yannick E. Bocko; Sarah Chadburn; et al. (Global Change Biology, 2023)
Peatlands of the central Congo Basin have accumulated carbon over millennia. They currently store some 29 billion tonnes of carbon in peat. However, our understanding of the controls on peat carbon accumulation and loss and the vulnerability of this stored carbon to climate change is in its infancy. Here we present a new model of tropical peatland development, DigiBog_Congo, that we use to simulate peat carbon accumulation and loss in a rain‐fed interfluvial peatland that began forming ~20,000 calendar years Before Present (cal. yr BP, where ‘present’ is 1950 CE). Overall, the simulated age‐depth curve is in good agreement with palaeoenvironmental reconstructions derived from a peat core at the same location as our model simulation. We find two key controls on long‐term peat accumulation: water at the peat surface (surface wetness) and the very slow anoxic decay of recalcitrant material. Our main simulation shows that between the Late Glacial and early Holocene there were several multidecadal periods where net peat and carbon gain alternated with net loss. Later, a climatic dry phase beginning ~5200 cal. yr BP caused the peatland to become a long‐term carbon source from ~3975 to 900 cal. yr BP. Peat as old as ~7000 cal. yr BP was decomposed before the peatland's surface became wetter again, suggesting that changes in rainfall alone were sufficient to cause a catastrophic loss of peat carbon lasting thousands of years. During this time, 6.4 m of the column of peat was lost, resulting in 57% of the simulated carbon stock being released. Our study provides an approach to understanding the future impact of climate change and potential land‐use change on this vulnerable store of carbon.

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

X-ray computed tomography: A novel non-invasive approach for the detection of microplastics in sediments? - Megan M. Trusler; Craig J. Sturrock; Christopher H. Vane; Sarah Cook; Barry H. Lomax (Marine Pollution Bulletin, 2023)

Bayesian and ultrasonic sensor aided multi-objective optimisation for sustainable clean-in-place processes - Alexander L. Bowler; Sarah Rodgers; David J. Cook; Nicholas J. Watson (Food and Bioproducts Processing, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Medical and healthcare waste generation, storage, treatment and disposal: a systematic scoping review of risks to occupational and public health - Ed Cook; Anne Woolridge; Petra Stapp; Sarah Edmondson; Costas A. Velis (Critical Reviews in Environmental Science and Technology, 2023)

Ancient bears provide insights into Pleistocene ice age refugia in Southeast Alaska - Flavio Augusto da Silva Coelho; Stephanie Gill; Crystal M. Tomlin; Marilena Papavassiliou; Sean D. Farley; Joseph A. Cook; Sarah A. Sonsthagen; George K. Sage; Timothy H. Heaton; Sandra L. Talbot; Charlotte Lindqvist (Molecular Ecology, 2023)
During the Late Pleistocene, major parts of North America were periodically covered by ice sheets. However, there are still questions about whether ice‐free refugia were present in the Alexander Archipelago along the Southeast (SE) Alaska coast during the last glacial maximum (LGM). Numerous subfossils have been recovered from caves in SE Alaska, including American black ( Ursus americanus ) and brown ( U. arctos ) bears, which today are found in the Alexander Archipelago but are genetically distinct from mainland bear populations. Hence, these bear species offer an ideal system to investigate long‐term occupation, potential refugial survival and lineage turnover. Here, we present genetic analyses based on 99 new complete mitochondrial genomes from ancient and modern brown and black bears spanning the last ~45,000 years. Black bears form two SE Alaskan subclades, one preglacial and another postglacial, that diverged >100,000 years ago. All postglacial ancient brown bears are closely related to modern brown bears in the archipelago, while a single preglacial brown bear is found in a distantly related clade. A hiatus in the bear subfossil record around the LGM and the deep split of their pre‐ and postglacial subclades fail to support a hypothesis of continuous occupancy in SE Alaska throughout the LGM for either species. Our results are consistent with an absence of refugia along the SE Alaska coast, but indicate that vegetation quickly expanded after deglaciation, allowing bears to recolonize the area after a short‐lived LGM peak.

SCAview: an Intuitive Visual Approach to the Integrative Analysis of Clinical Data in Spinocerebellar Ataxias - Mischa Uebachs; Philipp Wegner; Sebastian Schaaf; Simon Kugai; Heike Jacobi; Sheng-Han Kuo; Tetsuo Ashizawa; Juliane Fluck; Sophie Tezenas du Montcel; Peter Bauer; Paola Giunti; Arron Cook; et al. (The Cerebellum, 2023)
With SCAview, we present a prompt and comprehensive tool that enables scientists to browse large datasets of the most common spinocerebellar ataxias intuitively and without technical effort. Basic concept is a visualization of data, with a graphical handling and filtering to select and define subgroups and their comparison. Several plot types to visualize all data points resulting from the selected attributes are provided. The underlying synthetic cohort is based on clinical data from five different European and US longitudinal multicenter cohorts in spinocerebellar ataxia type 1, 2, 3, and 6 (SCA1, 2, 3, and 6) comprising > 1400 patients with overall > 5500 visits. First, we developed a common data model to integrate the clinical, demographic, and characterizing data of each source cohort. Second, the available datasets from each cohort were mapped onto the data model. Third, we created a synthetic cohort based on the cleaned dataset. With SCAview, we demonstrate the feasibility of mapping cohort data from different sources onto a common data model. The resulting browser-based visualization tool with a thoroughly graphical handling of the data offers researchers the unique possibility to visualize relationships and distributions of clinical data, to define subgroups and to further investigate them without any technical effort. Access to SCAview can be requested via the Ataxia Global Initiative and is free of charge.

Learning from arid and urban aquatic ecosystems to inform more sustainable and resilient futures - Lauren McPhillips; Marta Berbés-Blázquez; Rebecca Hale; Tamara K. Harms; Vanya Bisht; Liliana Caughman; Sandra M. Clinton; Elizabeth Cook; Xiaoli Dong; Jennifer Edmonds; Sarah Gergel; Rosa Gómez; et al. (Journal of Hydrology, 2023)

Integrating knowledge on green infrastructure, health and well-being in ageing populations: Principles for research and practice - Matthew Dennis; Adam Barker; Jamie Anderson; Jenna C. Ashton; Gina Cavan; Penny A. Cook; David French; Anna Gilchrist; Philip James; Christopher Phillipson; Konstantinos Tzoulas; C. Philip Wheater; et al. (Ambio, 2023)
Ageing and urbanisation pose significant challenges for public health and urban planning. Ageing populations are at particular risk from hazards arising from urbanisation processes, some of which are in turn exacerbated by climate change. One approach for mitigating the negative effects of urbanisation on ageing populations is the leveraging of the beneficial effects of urban green infrastructure as a public health intervention in the planning process. We assessed the potential of available theoretical frameworks to provide the context for such leverage. This involved active engagement with academics and practitioners specialising in ageing, green infrastructure and health and well-being through a knowledge-brokering approach. We concluded that an integrated and comprehensive framework on the socio-cultural-ecological determinants of health is lacking. To address this, we present a set of principles for overcoming challenges to knowledge integration when working at the intersection of green infrastructure, ageing, health and well-being. Our findings—and the co-production process used to generate them—have wider significance for trans-disciplinary research into the benefits of the natural environment to human health and well-being as well as other complex and interconnected topics associated with global grand challenges.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Review of adaptations of U.S. Commercial Fisheries in response to the COVID ‐19 pandemic using the Resist ‐ Accept ‐ Direct (RAD) framework - Sarah Lindley Smith; Samantha Cook; Abigail Golden; Mia Aiko Iwane; Danika Kleiber; Kirsten M. Leong; Anthony Mastitski; Laurie Richmond; Marysia Szymkowiak; Sarah Wise (Fisheries Management and Ecology, 2022)
The COVID‐19 pandemic transformed social and economic systems globally, including fisheries systems. Decreases in seafood demand, supply chain disruptions, and public safety regulations required numerous adaptations to maintain the livelihoods and social resilience of fishing communities. Surveys, interviews, and focus groups were undertaken to assess impacts from and adaptive responses to the pandemic in commercial fisheries in five U.S. regions: the Northeast, California, Alaska, the U.S. Caribbean, and the Pacific Islands. Fishery adaptation strategies were categorized using the Resist–Accept–Direct (RAD) framework, a novel application to understand social transformation in a social‐ecological system in response to a disturbance. A number of innovations emerged, or were facilitated, that could improve the fisheries' resilience to future disruptions. Fishers with diversified options and strategic flexibility generally fared better, i.e., had fewer disruptions to their livelihoods. Using the RAD framework to identify adaptation strategies from fishery system actors highlights opportunities for improving resilience of fisheries social‐ecological systems to future stressors.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Evolution of a hydrothermal ore-forming system recorded by sulfide mineral chemistry: a case study from the Plaka Pb–Zn–Ag Deposit, Lavrion, Greece - Max Frenzel; Panagiotis Voudouris; Nigel J. Cook; Cristiana L. Ciobanu; Sarah Gilbert; Benjamin P. Wade (Mineralium Deposita, 2022)
Laser ablation-inductively coupled plasma-mass spectrometry and electron-probe microanalysis were used to investigate the trace-element contents of sphalerite, chalcopyrite and pyrite from the Plaka Pb–Zn–Ag deposit. Using petrographic observations, the analytical results could be linked to the temporal evolution of the Plaka ore-forming system. Sphalerite chemistry reliably records the temperature and f S 2 evolution of the system, with estimated formation temperatures reproducing the microthermometric results from previous fluid-inclusion studies. Chalcopyrite chemistry also shows systematic variations over time, particularly for Cd, Co, Ge, In, Sn and Zn concentrations. Measurable pyrite was only found in association with early high-temperature mineralisation, and no clear trends could therefore be identified. We note, however, that As and Se contents in pyrite are consistent with formation temperatures estimated from co-existing sphalerite. Statistical analysis of the sphalerite data allowed us to identify the dominant geological controls on its trace-element content. The three investigated factors temperature, f S 2 , and sample location account for > 80% of the observed variance in Mn, Fe, Co, Ga, Ge, In, Sb and Hg concentrations, and > 60% of the observed variance in Cd and Sn concentrations. Only for Cu and Ag concentrations is the explained variance < 50%. A similarly detailed analysis was not possible for chalcopyrite and pyrite. Nevertheless, comparison of the results for all three investigated minerals indicates that there are some systematic variations across the deposit which may be explained by local differences in fluid composition.

Learning Together for and with the Martuwarra Fitzroy River - Rosemary Hill; Pia Harkness; Nat Raisbeck-Brown; Ilisapeci Lyons; Jorge G. Álvarez-Romero; Milena Kiatkoski Kim; Dennis Chungalla; Heather Wungundin; Mary Aiken; Jean Malay; Bernadette Williams; Rachel Buissereth; et al. (Sustainability Science, 2022)
Co-production across scientific and Indigenous knowledge systems has become a cornerstone of research to enhance knowledge, practice, ethics, and foster sustainability transformations. However, the profound differences in world views and the complex and contested histories of nation-state colonisation on Indigenous territories, highlight both opportunities and risks for Indigenous people when engaging with knowledge co-production. This paper investigates the conditions under which knowledge co-production can lead to improved Indigenous adaptive environmental planning and management among remote land-attached Indigenous peoples through a case study with ten Traditional Owner groups in the Martuwarra (Fitzroy River) Catchment in Western Australia’s Kimberley region. The research team built a 3D map of the river and used it, together with an interactive table-top projector, to bring together both scientific and Indigenous spatial knowledge. Participatory influence mapping, aligned with Traditional Owner priorities to achieve cultural governance and management planning goals set out in the Fitzroy River Declaration, investigated power relations. An analytical framework, examining underlying mechanisms of social learning, knowledge promotion and enhancing influence, based on different theories of change, was applied to unpack the immediate outcomes from these activities. The analysis identified that knowledge co-production activities improved the accessibility of the knowledge, the experiences of the knowledge users, strengthened collective identity and partnerships, and strengthened Indigenous-led institutions. The focus on cultural governance and management planning goals in the Fitzroy River Declaration enabled the activities to directly affect key drivers of Indigenous adaptive environmental planning and management—the Indigenous-led institutions. The nation-state arrangements also gave some support to local learning and decision-making through a key Indigenous institution, Martuwarra Fitzroy River Council. Knowledge co-production with remote land-attached Indigenous peoples can improve adaptive environmental planning and management where it fosters learning together, is grounded in the Indigenous-led institutions and addresses their priorities.

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Correction to: Biodiversity and Health in the Urban Environment - Melissa R. Marselle; Sarah J. Lindley; Penny A. Cook; Aletta Bonn (Current Environmental Health Reports, 2021)

Biodiversity and Health in the Urban Environment - Melissa R. Marselle; Sarah J. Lindley; Penny A. Cook; Aletta Bonn (Current Environmental Health Reports, 2021)
Purpose of review Biodiversity underpins urban ecosystem functions that are essential for human health and well-being. Understanding how biodiversity relates to human health is a developing frontier for science, policy and practice. This article describes the beneficial, as well as harmful, aspects of biodiversity to human health in urban environments. Recent findings Recent research shows that contact with biodiversity of natural environments within towns and cities can be both positive and negative to human physical, mental and social health and well-being. For example, while viruses or pollen can be seriously harmful to human health, biodiverse ecosystems can promote positive health and well-being. On balance, these influences are positive. As biodiversity is declining at an unprecedented rate, research suggests that its loss could threaten the quality of life of all humans. Summary A key research gap is to understand—and evidence—the specific causal pathways through which biodiversity affects human health. A mechanistic understanding of pathways linking biodiversity to human health can facilitate the application of nature-based solutions in public health and influence policy. Research integration as well as cross-sector urban policy and planning development should harness opportunities to better identify linkages between biodiversity, climate and human health. Given its importance for human health, urban biodiversity conservation should be considered as public health investment.

Indium distribution in sphalerite from sulfide–oxide–silicate skarn assemblages: a case study of the Dulong Zn–Sn–In deposit, Southwest China - Jing Xu; Nigel J. Cook; Cristiana L. Ciobanu; Xiaofeng Li; Alkiviadis Kontonikas-Charos; Sarah Gilbert; Youhu Lv (Mineralium Deposita, 2021)

Epidemiology, Clinical Features, and Management of Texas Coral Snake (Micrurus tener) Envenomations Reported to the North American Snakebite Registry - Spencer Greene; Anne-Michelle Ruha; Sharan Campleman; Jeffrey Brent; Paul Wax; Kim Aldy; Peter Akpunonu; Vikhyat S. Bebarta; Gillian A. Beauchamp; Michael C. Beuhler; Mary Billington; William Boroughf; et al. (Journal of Medical Toxicology, 2021)

Taxon pulse dynamics, episodic dispersal and host colonization across Beringia drive diversification of a Holarctic tapeworm assemblage - Genevieve M. S. Haas; Eric P. Hoberg; Joseph A. Cook; Heikki Henttonen; Arseny A. Makarikov; Sarah R. Gallagher; Nikolai E. Dokuchaev; Kurt E. Galbreath (Journal of Biogeography, 2020)
Aim We test the predictions of the Stockholm Paradigm, a synthesis of eco‐evolutionary theory explaining the nature of faunal assembly, host range and parasite diversification. Faunal diversification and assembly, manifested in patterns of host colonization, co‐adaptation and parasite speciation, are predicted to emerge as a consequence of alternating episodes of ecological disruption and stability. Specifically, for a diverse cestode genus ( Arostrilepis ), we evaluate the number and direction of Pleistocene dispersal events across Beringia, the number and relative timing of host colonization events and the relationship between host and parasite biogeographic histories and associations through time. Location Beringia and adjacent temperate to arctic biomes in North America and Eurasia. Taxon Arostrilepis (Cyclophyllidea: Hymenolepididae) and its rodent hosts. Methods Multi‐locus phylogenetic reconstruction and biogeographic ancestral range estimation. Results Arostrilepis lineages crossed Beringia eastward into North America a minimum of four times and westward into Asia twice in association with temporally disjunct geographic expansions of three major tribes of cricetid rodents (Arvicolini, Myodini, Lemmini). Inferences of ancestral host associations support at least nine instances of host colonization involving shifts from one rodent tribe or family to another. Several previously unrecognized lineages of Arostrilepis are revealed. Main conclusions Consistent with expectations of the Stockholm Paradigm, episodes of intercontinental dispersal were both frequent in the history of Arostrilepis and preceded a majority of inferred host‐colonization events. Events of historical geographic expansion created numerous opportunities for development of novel host–parasite associations through ecological fitting, as parasites tracked historically conserved resources available across diverse host taxa. Beringia played a major role in shaping rodent/parasite assemblages by mediating dispersal between the northern continents during glacial episodes of the Pleistocene, rather than by serving as a zone of refugial isolation.

Conjoint use of hydraulic head and groundwater age data to detect hydrogeologic barriers - Sarah K. Marshall; Peter G. Cook; Leonard F. Konikow; Craig T. Simmons; Shawan Dogramaci (Hydrogeology Journal, 2020)

Spiraling Down Hillslopes: Nutrient Uptake from Water Tracks in a Warming Arctic - Tamara K. Harms; Christopher L. Cook; Adam N. Wlostowski; Michael N. Gooseff; Sarah E. Godsey (Ecosystems, 2019)

Estimating aboveground net biomass change for tropical and subtropical forests: Refinement of IPCC default rates using forest plot data - Daniela Requena Suarez; Danaë M. A. Rozendaal; Veronique De Sy; Oliver L. Phillips; Esteban Alvarez‐Dávila; Kristina Anderson‐Teixeira; Alejandro Araujo‐Murakami; Luzmila Arroyo; Timothy R. Baker; Frans Bongers; Roel J. W. Brienen; Sarah Carter; et al. (Global Change Biology, 2019)
As countries advance in greenhouse gas (GHG) accounting for climate change mitigation, consistent estimates of aboveground net biomass change (∆AGB) are needed. Countries with limited forest monitoring capabilities in the tropics and subtropics rely on IPCC 2006 default ∆AGB rates, which are values per ecological zone, per continent. Similarly, research into forest biomass change at a large scale also makes use of these rates. IPCC 2006 default rates come from a handful of studies, provide no uncertainty indications and do not distinguish between older secondary forests and old‐growth forests. As part of the 2019 Refinement to the 2006 IPCC Guidelines for National Greenhouse Gas Inventories, we incorporate ∆AGB data available from 2006 onwards, comprising 176 chronosequences in secondary forests and 536 permanent plots in old‐growth and managed/logged forests located in 42 countries in Africa, North and South America and Asia. We generated ∆AGB rate estimates for younger secondary forests (≤20 years), older secondary forests (>20 years and up to 100 years) and old‐growth forests, and accounted for uncertainties in our estimates. In tropical rainforests, for which data availability was the highest, our ∆AGB rate estimates ranged from 3.4 (Asia) to 7.6 (Africa) Mg ha −1 year −1 in younger secondary forests, from 2.3 (North and South America) to 3.5 (Africa) Mg ha −1 year −1 in older secondary forests, and 0.7 (Asia) to 1.3 (Africa) Mg ha −1 year −1 in old‐growth forests. We provide a rigorous and traceable refinement of the IPCC 2006 default rates in tropical and subtropical ecological zones, and identify which areas require more research on ∆AGB. In this respect, this study should be considered as an important step towards quantifying the role of tropical and subtropical forests as carbon sinks with higher accuracy; our new rates can be used for large‐scale GHG accounting by governmental bodies, nongovernmental organizations and in scientific research.

Acoustic Backscatter Patterns - Jaime Palter; Lauren Cook; Alfonso Goncalves Neto; Sarah Nickford; Danielle Bianchi (Oceanography, 2019)

Population Pharmacokinetic Modeling in the Presence of Missing Time-Dependent Covariates: Impact of Body Weight on Pharmacokinetics of Paracetamol in Neonates - Wojciech Krzyzanski; Sarah F. Cook; Melanie Wilbaux; Catherine M. T. Sherwin; Karel Allegaert; An Vermeulen; John N. van den Anker (The AAPS Journal, 2019)

3D Printing of Metformin HCl PVA Tablets by Fused Deposition Modeling: Drug Loading, Tablet Design, and Dissolution Studies - Mariam Ibrahim; Morgan Barnes; Robert McMillin; Daniel W. Cook; Sarah Smith; Mathew Halquist; Dayanjan Wijesinghe; Thomas D. Roper (AAPS PharmSciTech, 2019)

Training Needs of Clinical and Research Professionals to Optimize Minority Recruitment and Retention in Cancer Clinical Trials - Soumya J. Niranjan; Raegan W. Durant; Jennifer A. Wenzel; Elise D. Cook; Mona N. Fouad; Selwyn M. Vickers; Badrinath R. Konety; Sarah B. Rutland; Zachary R. Simoni; Michelle Y. Martin (Journal of Cancer Education, 2019)

Baseline results from the UK SIGNIFY study: a whole-body MRI screening study in TP53 mutation carriers and matched controls - Sibel Saya; Emma Killick; Sarah Thomas; Natalie Taylor; Elizabeth K. Bancroft; Jeanette Rothwell; Sarah Benafif; Alexander Dias; Christos Mikropoulos; Jenny Pope; Anthony Chamberlain; Ranga Gunapala; et al. (Familial Cancer, 2017)

Disease Progression Modeling: Key Concepts and Recent Developments - Sarah F. Cook; Robert R. Bies (Current Pharmacology Reports, 2016)

Effects of Paclitaxel and Eribulin in Mouse Sciatic Nerve: A Microtubule-Based Rationale for the Differential Induction of Chemotherapy-Induced Peripheral Neuropathy - Sarah J. Benbow; Brett M. Cook; Jack Reifert; Krystyna M. Wozniak; Barbara S. Slusher; Bruce A. Littlefield; Leslie Wilson; Mary Ann Jordan; Stuart C. Feinstein (Neurotoxicity Research, 2016)

A Framework for Quantitative Assessment of Impacts Related to Energy and Mineral Resource Development - Seth S. Haines; Jay E. Diffendorfer; Laurie Balistrieri; Byron Berger; Troy Cook; Don DeAngelis; Holly Doremus; Donald L. Gautier; Tanya Gallegos; Margot Gerritsen; Elisabeth Graffy; Sarah Hawkins; et al. (Natural Resources Research, 2014)

China as a new shaper of international development: the environmental implications - Frauke Urban; Giles Mohan; Sarah Cook (Environment, Development and Sustainability, 2013)

Multivariate Analysis of an LA-ICP-MS Trace Element Dataset for Pyrite - Lyron Winderbaum; Cristiana L. Ciobanu; Nigel J. Cook; Matthew Paul; Andrew Metcalfe; Sarah Gilbert (Mathematical Geosciences, 2012)

Qualitative detection of the NSAIDs diclofenac and ibuprofen in the hair of Eurasian otters (Lutra lutra) occupying UK waterways with GC–MS - Ngaio L. Richards; Gemma Cook; Vic Simpson; Sarah Hall; Nancy Harrison; Karen S. Scott (European Journal of Wildlife Research, 2011)

Interaction between inflammation-related gene polymorphisms and cigarette smoking on the risk of myocardial infarction in the Physician’s Health Study - Sarah A. Rosner; Paul M. Ridker; Robert Y. L. Zee; Nancy R. Cook (Human Genetics, 2005)